FGFR2 and favorable survival outcomes in resected poorly cohesive cell gastric cancer: Analysis from FGFR2 protein overexpression and genetic variation - Yun Ji Lee; Inuk Jung; Jin Ho Baek; Jong Gwang Kim; Ki Bum Park; Ji Yeon Park; Oh Kyoung Kwon; An Na Seo; Moonsik Kim; Byung Woog Kang (PLoS ONE, 2026)
Purpose Poorly cohesive cell gastric cancer has aggressive and heterogeneous characteristics. This study investigated the clinical significance of fibroblast growth factor receptor 2 expression and genetic variations in patients with PCC-GC. Materials and Methods We retrospectively collected 209 surgically resected stage II and III PCC-GC cases. After FGFR2 immunostaining, we analyzed clinical data and performed targeted sequencing to assess their impact on patient survival. Results Among 209 patients, 89 (42.6%) were classified as stage II and 120 (57.4%) as stage III. FGFR2 overexpression varied by stage, with FGFR2 positivity observed in 61.5% of stage II cases, while FGFR2-negative cases were predominant in stage III patients (60.1%) (P = 0.037). Moreover, lymph node involvement was associated with FGFR2 expression (P = 0.009). FGFR2 positivity significantly correlated with improved disease-free survival (DFS) and overall survival and remained an independent favorable prognostic factor for DFS in multivariate analysis (P = 0.022). Targeted next-generation sequencing was performed in five selected cases, FGFR2 amplification or pathogenic alterations were not found. Conclusion This study shows that FGFR2 expression was independently associated with improved DFS in PCC-GC. These findings suggest that FGFR2 may serve as a prognostic biomarker in patients with PCC-GC.